Effects of visceral manipulation in the treatment of pain in women with primary dysmenorrhea (Research, Society and Development, 2021)
Objective: This study aimed to evaluate the effects of visceral manipulation in the treatment of pain in women with primary dysmenorrhea. Method: This is a cross-sectional randomized clinical trial study, in which 13 women with primary dysmenorrhea were evaluated. Initially, a socio-clinical data collection was performed, then a questionnaire on dysmenorrhea was applied and pain intensity was assessed using the Visual Analog Scale (VAS). They were divided into two groups, one of them being the control group (CG) that used Tens Burst and the experimental group (EG) in which visceral manipulations of the uterus and ovaries were performed. After the end of the consultations, the patients were re-evaluated with the same questionnaire and scale already used. Results: It was possible to observe from the data that although both groups had positive results after the treatment period, the EG showed a more significant improvement in terms of pain intensity and symptom reduction, when compared to the CG after both techniques, especially in the initial phase of the menstrual cycle. It was also observed in the EG a pain reduction of 3.85 points in the VAS after visceral manipulation, whereas in the CG it obtained a pain reduction in the VAS of 0.83 points when using TENS. Conclusion: Therefore, both techniques showed satisfactory results, however visceral manipulation showed more positive results, especially in the initial phase of menstruation, being able to reduce pain in women with dysmenorrhea.